Dampak serangan siber dan kebocoran data pada perbankan syariah terhadap tingkat kepercayaan nasabah - Ardhian, Ivan Rizal Nur (Maliki Interdisciplinary Journal, 2023)
Banks are monetary organizations that assume a significant part for the Indonesian economy as of now, the utilization of banking is expanding on the grounds that everything should be possible utilizing cell phones, Web Banking, ATM machines, and tellers at bank office workplaces. From beginning with day to day needs and involving them for exchanges with individual clients of a similar bank or others. Morally, these financial establishments ought to safeguard the security information of clients who utilize their administrations. Nonetheless, it can’t be rejected that there are instances of information spillage, one of which was capable by PT. Bank Syariah Indonesia and obviously disregards the standards of information security, information protection and morals. The presence of an information burglary rationale causes a deficiency of classification, protection, accessibility, and respectability of PT. Bank Syariah Indonesia and causes misfortunes both material and non-material. This study means to apply lawful security for purchasers of PT. Bank Syariah Indonesia and the obligations of business entertainers towards customers in financial administrations at PT. Indonesian Sharia Bank. By raising this issue, it is trusted that we will be generally more mindful of the dangers of digital assaults that undermine the financial business, including sharia banking.